Phragmites karka as a Biosorbent for the Removal of Mercury Metal Ions from Aqueous Solution: Effect of Modification - Muhammad Hamid Raza; Aqsa Sadiq; Umar Farooq; Makshoof Athar; Tajamal Hussain; Adnan Mujahid; Muhammad Salman (Journal of Chemistry)
Batch scale studies for the adsorption potential of novel biosorbent Phragmites karka (Trin), in its natural and treated forms, were performed for removal of mercury ions from aqueous solution. The study was carried out at different parameters to obtain optimum conditions of pH, biosorbent dose, agitation speed, time of contact, temperature, and initial metal ion concentration. To analyze the suitability of the process and maximum amount of metal uptake, Dubinin-Radushkevich (D-R) model, Freundlich isotherm, and Langmuir isotherm were applied. The values of qmax for natural and treated biosorbents were found at 1.79 and 2.27 mg/g, respectively. The optimum values of contact time and agitation speed were found at 50 min and 150 rpm for natural biosorbent whereas 40 min and 100 rpm for treated biosorbent, respectively. The optimum biosorption capacities were observed at pH 4 and temperature 313 K for both natural P. karka and treated P. karka. RL values indicate that comparatively treated P. karka was more feasible for mercury adsorption compared to natural P. karka. Both pseudo-first-order and pseudo-second-order kinetic models were applied and it was found that data fit best to the pseudo-second-order kinetic model. Thermodynamic studies indicate that adsorption process was spontaneous, feasible, and endothermic.